2022
DOI: 10.1097/sla.0000000000005616
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Risk Prediction Model of 90-day Mortality After Gastrectomy for Cancer

Abstract: Objective: To develop and validate a risk prediction model of 90-day mortality (90DM) using machine learning in a large multicenter cohort of patients undergoing gastric cancer resection with curative intent. Background: The 90DM rate after gastrectomy for cancer is a quality of care indicator in surgical oncology. There is a lack of well-validated instruments for personalized prognosis of gastric cancer. Methods: Consecutive patients with gastric adenocarcinoma who underwent potentially curative gastrectomy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
(96 reference statements)
1
10
0
Order By: Relevance
“…Twenty-three articles9,19,21,23–25,27,29,30,32–34,36,37,39,41,42,44–46,48–50 (63.9%) reported precision metrics (area under the precision-recall curve, positive predictive value, or F1 score). Twenty-five articles9,20,21,23–28,31,33,34,36,38,40,42–50 (69.4%) included explainability mechanisms to convey the relative importance of input features in determining outputs. Thirteen articles9,16,17,20,25,27,29,30,35,38,45,46,50 (36.1%) presented a framework that could be used for clinical implementation; none of the articles assessed the efficacy of clinical implementation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-three articles9,19,21,23–25,27,29,30,32–34,36,37,39,41,42,44–46,48–50 (63.9%) reported precision metrics (area under the precision-recall curve, positive predictive value, or F1 score). Twenty-five articles9,20,21,23–28,31,33,34,36,38,40,42–50 (69.4%) included explainability mechanisms to convey the relative importance of input features in determining outputs. Thirteen articles9,16,17,20,25,27,29,30,35,38,45,46,50 (36.1%) presented a framework that could be used for clinical implementation; none of the articles assessed the efficacy of clinical implementation.…”
Section: Resultsmentioning
confidence: 99%
“…The average AUROC for the best model across all 36 articles was 0.83; of the 8 articles with sample sizes of less than 2000 (ie, less than 1000 samples per class), 7 22,[26][27][28]31,35,37 (87.5%) had below-average (ie, less than 0.83) AUROC or accuracy. Twenty-four 9,18,20,[24][25][26][27][28][29][32][33][34][35]37,[39][40][41][43][44][45][46][47][48][49] articles (66.7%) presented confidence intervals for performance metrics. Among the 8 articles with sample sizes of less than 2000, 5 [26][27][28]35,37 presented confidence intervals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have tried to use ML models to optimize postoperative management by predicting postoperative complications. Unfortunately, many conclude that the implementation of these models is far from being clinically viable, even though most ML models achieve reasonable performance [5][6][7][8][9][10][11][12][13][14][15]. Cao et al [5], Weller et al [12], and Van den Bosch et al [15] concluded that no practical implementation could be achieved for ML models due to the predictive value being too low to clinically implement.…”
Section: Barriers and Solutionsmentioning
confidence: 99%
“…Most risk prediction models in the literature were developed using multivariable logistic regression models or ML techniques to predict a binary outcome. Aside from the AutoScore framework, ML applications include the use of Naive Bayes (NB), XGBoost, k-nearest neighbor (K-NN), multilayer perceptron, support vector machine (SVM) and CatBoost for predicting the risk of cardiovascular disease [ 21 ], random forest (RF), XGBoost, logistic regression, SVM and K-NN for the risk of incident diabetic retinopathy among patients with type 2 diabetes mellitus [ 22 ], a stroke risk prediction model using NB, decision tree and RF models [ 23 ], a XGBoost based cerebral infarction risk prediction model [ 24 ], and a developed risk model for 90-day mortality of patients undergoing gastric cancer resection with curative intent using cross validated elastic regularized logistic regression method, boosting linear regression, RF and an ensemble model [ 25 ].…”
Section: Introductionmentioning
confidence: 99%